The Application of Global Positioning System (GPS) in Mapping Survey of Historical and Archeological Site - Khakhim, Nurul (Forum Geografi, 2002)
Technical development of Global Positioning System (GPS) is the positional determination system of ground control point in the earth surface, which based on satellite. It leads to the signiï¬cant influence on the methodological aspect of positional determination survey in the earth surface. Global Positioning System gives the three dimension position (X, K Z) or longitudinal, latitude and altitude which are formulated in the reference of World Geodetic System (WGS) in 1984. The data characteristic is the ï¬rst data, which is required in the survey of limit mapping of historical and archeological site. This article tries to explain the possibility of using the technology of Global Positioning System (GPS) to map the archeological site which contains of potential, ohstacle, methodology and case study in Boko Prambanan temple area. It is also utilized to the possibility of using the Geographical Information System (GIS) to analyze the spatial existence site of environmental condition.